2019
DOI: 10.3390/su11195170
|View full text |Cite
|
Sign up to set email alerts
|

Working in a Physically Dangerous Work Environment: Employee Vitality and Sustainable Behavior

Abstract: There is a limited understanding of the antecedents and consequences of employee vitality during war zone exposure. The current study is one of the first ones to investigate the direct effects of perceived danger on employee vitality by collecting data from Afghanistan, one of the most dangerous countries in the world. Furthermore, it was investigated how employee vitality affects sustainable behavior at the workplace. The hypotheses of the study have been tested by using data from two surveys collected from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
2
4
0
Order By: Relevance
“…Environmental and psychological safety is important for employees' happiness and vitality at the workplace (Kark & Carmeli, ). Supporting our arguments, Jahanshahi, Brem, & Gholami, () have found that employees' aliveness and vitality are lower among those working in a physically dangerous work environment. Therefore we hypothesized that a high level of fear (perceived danger) threatens the quality of employees' work life and eventually leads to the decline of the employees' sense of well‐being.H1 There is a negative and significant impact between perceived danger and employees' well‐being.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 83%
“…Environmental and psychological safety is important for employees' happiness and vitality at the workplace (Kark & Carmeli, ). Supporting our arguments, Jahanshahi, Brem, & Gholami, () have found that employees' aliveness and vitality are lower among those working in a physically dangerous work environment. Therefore we hypothesized that a high level of fear (perceived danger) threatens the quality of employees' work life and eventually leads to the decline of the employees' sense of well‐being.H1 There is a negative and significant impact between perceived danger and employees' well‐being.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 83%
“…Employees with high environmental awareness can identify the costs and benefits linked with environment-related issues and tend to become involved in eco-friendly behaviors in the workplace. Further, environmentally aware employees pay close attention to environmental challenges and tend to exhibit sustainability-oriented behaviors at the workplace [62]. Usually, individuals do not become involved in situations about which they have limited knowledge, and they tend to avoid these situations [17].…”
Section: Moderation Of Environmental Awarenessmentioning
confidence: 99%
“…While discrimination is associated with poorer well‐being (Deitch et al, 2003) and greater stress (Pascoe & Smart Richman, 2009), feelings of inclusion predict enthusiasm and vitality (Warren et al, 2021). Vitality, or a sense of liveliness, is valuable for women's careers because it is associated with workplace well‐being (Ryan & Frederick, 1997; van Scheppingen et al, 2015), productivity and motivation (Afshar Jahanshahi et al, 2019; Ryan & Deci, 2008). Past research shows that work relationships impact employee's feelings of vitality (Carmeli, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%